2016
DOI: 10.1073/pnas.1609569114
|View full text |Cite|
|
Sign up to set email alerts
|

Clarifying intact 3D tissues on a microfluidic chip for high-throughput structural analysis

Abstract: On-chip imaging of intact three-dimensional tissues within microfluidic devices is fundamentally hindered by intratissue optical scattering, which impedes their use as tissue models for high-throughput screening assays. Here, we engineered a microfluidic system that preserves and converts tissues into optically transparent structures in less than 1 d, which is 20× faster than current passive clearing approaches. Accelerated clearing was achieved because the microfluidic system enhanced the exchange of intersti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 33 publications
1
48
0
Order By: Relevance
“…Moreover, increasing the acrylamide concentration decreases the extent of tissue shrinkage (e.g., 80-90% of the spheroids initial volume was maintained when used 8% (w/v) acrylamide). On the other hand, SDS solution flow led to the lipophilic dye (DiO) fluorescence loss but simultaneously did not affect the spheroids stain with Transferrin-647 as well as facilitated the spheroids staining with DAPI and Phalloidin-488 (Chen et al, 2016). The results obtained also demonstrated that the imaging depth was increased by 150% for MCF-7 spheroids (labeled with CellTracker™ Red), and 250% for U87MG-GFP spheroids, when compared to the noncleared spheroids.…”
Section: Clarity and Derived Methodsmentioning
confidence: 87%
See 3 more Smart Citations
“…Moreover, increasing the acrylamide concentration decreases the extent of tissue shrinkage (e.g., 80-90% of the spheroids initial volume was maintained when used 8% (w/v) acrylamide). On the other hand, SDS solution flow led to the lipophilic dye (DiO) fluorescence loss but simultaneously did not affect the spheroids stain with Transferrin-647 as well as facilitated the spheroids staining with DAPI and Phalloidin-488 (Chen et al, 2016). The results obtained also demonstrated that the imaging depth was increased by 150% for MCF-7 spheroids (labeled with CellTracker™ Red), and 250% for U87MG-GFP spheroids, when compared to the noncleared spheroids.…”
Section: Clarity and Derived Methodsmentioning
confidence: 87%
“…On the other hand, SDS solution flow led to the lipophilic dye (DiO) fluorescence loss but simultaneously did not affect the spheroids stain with Transferrin-647 as well as facilitated the spheroids staining with DAPI and Phalloidin-488 (Chen et al, 2016). On the other hand, SDS solution flow led to the lipophilic dye (DiO) fluorescence loss but simultaneously did not affect the spheroids stain with Transferrin-647 as well as facilitated the spheroids staining with DAPI and Phalloidin-488 (Chen et al, 2016).…”
Section: Clarity and Derived Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To address this issue, Chan and colleagues recently developed an imaging-on-a-chip system to achieve optical clearing and high-resolution imaging of optically transparent structures of intact tumor spheroids [72]. With the built-in fluid exchange capability of this microfluidic chip, multiple tumor spheroids could be cleared within 1 day by removing the scattering lipid molecules post crosslinking, allowing for high-throughput tissue imaging of intact organoids, analyses of tumor biomarkers and microstructures, and, potentially, investigations of nanomedicine-cancer organoid interactions.…”
Section: Discussionmentioning
confidence: 99%